Keluarga sebagai Pilar Perdamaian: Analisis Pendidikan Karakter, Pendidikan Multikultural, dan Filosofi Tembang Macapat - Nugroho, Yulius Setyo (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2024)
AbstractThis research explores the values of peace that come from character education, multicultural education, and the philosophy of tembang macapat for developing peace through peace education in the family. This research uses a qualitative method by conducting literature analysis and philosophical analysis of tembang macapat on the YouTube channel. The results showed that first, peace education has four core concepts as a “big umbrella” to develop peace education in a small or local scope, namely: positive peace and negative peace, peace education as a transformative practice, non-violence, and a culture of peace; second, peace education values in the family are categorized into three groups, namely: primary group, secondary group, and tertiary group. Although categorized into three groups, it does not mean that the three have a hierarchical position, one is more important than the other because the categorization effort aims to show the connection of the values obtained from the three different sources; and third, the family is the pillar of peace, so building peace must start from the family. Therefore, peace education in the family must be prepared seriously, considering the microsystem, ecosystem, and macrosystem aspects. Thus, peace education in the family will be more holistic (relevant, contextual, and transformative).